Dynamics of magnetic evaporative beamline cooling for the preparation of cold atomic beams - Ashtari Esfahani, Ali; Spanier, Felix (Physical review, 2025)
The most sensitive direct neutrino mass searches today are based on measurement of the end point of the 𝛽 spectrum of tritium to infer limits on the mass of the unobserved neutrino. To avoid the smearing associated with the distribution of molecular final states in the T-He molecule, the next generation of these experiments will need to employ atomic (T) rather than molecular (T2) tritium sources, at currents of at least 1015 atoms per second. Following production, atomic T can be trapped in gravitational and/or magnetic bottles for 𝛽 spectrum experiments, if and only if it can first be cooled to millikelvin temperatures. Accomplishing this cooling presents substantial technological challenges. The Project 8 collaboration is developing a technique based on magnetic evaporative cooling along a beamline (MECB) for the purpose of cooling T to feed a magnetogravitational trap that also serves as a cyclotron radiation emission spectroscope. Initial tests of the approach are planned in a pathfinder apparatus using atomic Li. This paper presents a method for analyzing the dynamics of the MECB technique and applies these calculations to the design of systems for cooling and slowing of atomic Li and T. A scheme is outlined that could provide a current of T at the millikelvin temperatures required for the Project 8 neutrino mass search.
Gesehen am 19.02.2026